A Fuzzy-Set Analysis of Conservative Agriculture Practice Adoption: Role of Farmer Orientations and Attitude - Hayat, Naeem; Al Mamun, Abdullah; Salameh, Anas A.; Yang, Qing; Zainol, Noor Raihani; Makhbul, Zafir Khan Mohamed (Frontiers in Psychology, 2022)
Conservative agriculture practices (CAPs) adoption literature advocates that adoption is caused by the many factors comprising cognitive, social, economic, personal, and CAPs related factors. Evaluating the adoption of CAPs as the outcome is complex and challenging with regression-based models as the systemic interdependencies of the factors offer diverse or varying results. Farmer production and environmental orientations as cognitive stances are notable interpreters of CAP adoption.The appetite level for risk-taking, innovativeness, and trust facilitates the adoption of CAPs. However, a causal-predictive technique should be used to investigate the adoption of CAP.Hence, the current study engages in a configuration approach using a fuzzy set Qualitative Comparative Analysis (fs/QCA) to analyse the patterns of different types of farmers’ orientations, personal level of trust on extension services, and innovativness risk-taking attitude on the intention to adopt CAPs. The analysis is based on the 155-farmer data collected employing a structured interview from Pakistan. The results suggest that a higher level of environment orientation and innovativeness are sufficient to increase intention to adopt CAPs. Moreover, a higher intention to adopt CAPs is achieved with a lower production orientation, a higher personal level of innovativeness, and a risk-taking attitude of the farmer. The innovativeness can help to develop the intention to adopt the CAPs among the environment and production-oriented farmers. Causal solutions offer a unique understanding that the farmers’ environment and production orientation can combine to suggest inclined to adopt CAPs by having an attitude of innovativeness and risk-taking. The causal solutions achieved significant predictive validity in the holdout samples. Policy and farmer-level suggestions were made to raise the intention to adopt CAPs among the farmers.